The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1177/073346402237631
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Perceived Social Support Among Live-Alone Urban Elders

Abstract: The relationship of cognition to perceived social support (PSS) was examined in a sample of 188 older medical patients who lived alone before admission to the hospital. Most of the patients were African American, and a majority (54.3%) was classified as cognitively impaired based on their performance on the Mattis Dementia Rating Scale. Compared with cognitively intact elders, impaired participants reported lower overall PSS as well as lower PSS in their relationships with friends and significant others. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
(37 reference statements)
2
19
0
Order By: Relevance
“…This study found a significant relationship between social support and cognitive function, consistent with previous findings that elders with more social support had better cognitive function (Kawachi & Berkman 2001, Seeman et al. 2001, Ficker et al. 2002, Zunzunegui et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study found a significant relationship between social support and cognitive function, consistent with previous findings that elders with more social support had better cognitive function (Kawachi & Berkman 2001, Seeman et al. 2001, Ficker et al. 2002, Zunzunegui et al.…”
Section: Discussionsupporting
confidence: 92%
“…In Western countries, many studies suggest that social support plays an important role in maintaining elders’ cognitive function (Kawachi & Berkman 2001, Seeman et al. 2001, Ficker et al. 2002, Zunzunegui et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate but related literature, objective measures of cognition suggest that factors such as depression and low social support are associated with poor cognitive skills (Ficker, MacNeill, Bank, & Lichtenberg, 2002; Fishbain, Cutler, Rosomoff, & Rosomoff, 1997). One study focused on how health and chronic pain impact cognition and found that mental flexibility is particularly vulnerable, a skill that is vital for elders to maintain independence (Karp et al, 2006).…”
Section: Subjective Memory Complaints Vs Perceived Cognitive Impairmentmentioning
confidence: 99%
“…A person's perception of the adequacy or quality of support is inevitably influenced by his or her expectation of the type, frequency and source of support preferred or required (Reinhardt & Blieszner 2000). There is evidence that what individuals expect from formal and informal sources of support varies and influences fundamentally their assessment of the adequacy or quality of support received (Ward 1985, Sinclair et al . 1988, Ficker et al .…”
Section: Introductionmentioning
confidence: 99%